Nutritional status, poverty, and relative deprivation among socio-economic and gender groups in India: Is the growth inclusive?. (June 2020) - Bhuyan, Biswabhusan; Sahoo, Bimal Kishore; Suar, Damodar
Highlights: India has achieved high economic success lately, but it has not translated to reduce prevalence of calorie deprivation. The incidence of nutritional poverty has been soaring and it has adversely affected economic weaker sections and the marginalised socio-religious, and gender groups in India. The results are consistent and robust to use of alternate recommended dietary allowance and adjusted calorie intake. The findings do not support the inclusiveness of India's high growth narrative. Abstract: India has witnessed high economics growth from the beginning of the new millennium. The agriculture and allied sector also recorded the highest growth during 2003–4 to 2012–13, coupled with marked improvement in production. It is now a food surplus and net-exporter country from food deficit since the mid-1990s. This should have result in lower incidence of poverty and calorie deprivation. However, the realisation of the growth went on the contrary to the general expectation by driving inequality and increasing deprivation. The prevalence of direct poverty remained high, which is a serious concern for achieving inclusive growth. This study examined nutritional status, direct and indirect poverty, and relative deprivation among socio-economic, and gender groups in India using national sample survey data. Albeit considering meals consumed outside the home, the results bespeak that nutritional status has been deteriorating. The incidence of nutritional poverty has been ascending since 2004–5 and adversely affected economic weaker sections and the marginalised socio-religious, and gender groups. They remained most deprive section of the society. The results are consistent and robust to use of alternate recommended dietary allowance and adjusted calorie intake, which takes into account under-reporting of food consumed away from home. Above findings question the inclusiveness of India's high growth narrative.